Code Mixing As Woman Identity: A Case on Instagram Captions of Influencer - Asma Alhusna; Noni Febriana (Fakultas Sastra Universitas Ekasakti, 2022)
This paper deals with the fact that special code mixing is used by every people for their caption. Include the Influencer. They promoting the products on Instagram using unique, chic, and fancy captions that will make their fans interested. The code mixing, which is employed in this case involve words or phrases identified as woman language. The data were taken from documented captions, which accompany the Influencers with the most people love their photos from Indonesia. The data focuse on Indonesian clauses or sentence mixed by English language. The result of study demonstrates that code mixing in the captions is the woman language features; empty adjective, special color terms, hashtags, polite form and sweet clossing, used by women but commonly avoided by men. In this case, those features as a certain group with distinctive language features. Internal and external factors determine the process of certain language features to be a marker of the group as well.